Mechanism of Anticonvulsant Action of ACTH - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2001)
The hypothesis that systemic or intraventricular administration of corticotropin (ACTH) acts directly on limbic neurons to modulate corticotropin-releasing hormone (CRH) gene expression, independently of adrenal stimulation, was tested and confirmed in experiments on developing rats (9-11 days postnatal) at the University of California, Irvine.